2007
DOI: 10.1111/j.1442-2042.2007.01739.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of renal cell carcinoma: A nation‐wide survey in Japan, 2002

Abstract: Objective: To investigate the incidence of renal cell carcinoma, classified by sex, age group and region in Japan, following a 5-year interval after a previous survey performed in 1997. Methods:The survey was conducted between the beginning of January 2002 and the end of December 2002. A total of 1288 institutions in all 47 prefectures throughout Japan were requested to register cases. Results: There were 7405 persons with renal cell carcinoma, consisting of 5063 males and 2342 females. Crude incidence rates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…The average age of HCVpositive patients with RCC was significantly younger than that of HCV-negative patients with RCC, a cancer that generally affects older individuals (15). Our findings validate previously published reports (10,16) suggesting that older age and African-American race are independent risk factors for RCC. Our findings thus corroborate our own clinical observations and seropositivity data, as well as frequent anecdotal reports in the literature that have strongly suggested an association between chronic HCV infection and RCC (11)(12)(13)(14)17).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The average age of HCVpositive patients with RCC was significantly younger than that of HCV-negative patients with RCC, a cancer that generally affects older individuals (15). Our findings validate previously published reports (10,16) suggesting that older age and African-American race are independent risk factors for RCC. Our findings thus corroborate our own clinical observations and seropositivity data, as well as frequent anecdotal reports in the literature that have strongly suggested an association between chronic HCV infection and RCC (11)(12)(13)(14)17).…”
Section: Discussionsupporting
confidence: 82%
“…Numerous reports have detailed this phenomenon, with increasing RCC rates described globally (7), and in the United States (6), Europe (8), Ireland (9), and Japan (10). Strong and reproducible risk factors for developing RCC have not been identified, but high body mass index, tobacco use, and, to a lesser extent, CKD have been implicated.…”
Section: Introductionmentioning
confidence: 99%
“…23 Also Marumo et al shows an increased incidence in this country and the need to study its relationship with known risk factors. 24 Similarly, Yang et al…”
Section: Asia and Oceaniamentioning
confidence: 99%
“…In Japan, a previous nationwide study investigating RCC revealed 7,405 patients (5,063 males, 2,342 females) with a positive diagnosis in 2002 (2).…”
Section: Introductionmentioning
confidence: 99%